Stabilization of moduli in spacetime with nested warping and the UED - Mathew Thomas Arun (Nuclear Physics B, 2017)
The absence, so far, of any graviton signatures at the LHC imposes severe constraints on the Randall–Sundrum scenario. Although a generalization to higher dimensions with nested warpings has been shown to avoid these constraints, apart from incorporating several other phenomenologically interesting features, moduli stabilization in such models has been an open question. We demonstrate here how both the moduli involved can be stabilized, employing slightly different mechanisms for the two branches of the theory. This also offers a dynamical mechanism to generate and stabilise the scale for the Universal Extra Dimensions, another long-standing issue.